The Impacts of Microsocial Relationships on School Mobility in the Roma Population - Elekes, Györgyi (Szociológiai Szemle, 2023)
In my paper I analyse action strategies observed among the successful Roma with the aid of the narrative interview technique developed primarily by Gabriele Rosenthal, based on Oevermann’s objective hermeneutics approach. The goal of the analysis was to integrate the typical coping strategies and patterns of adaptation obtained from hermeneutical case reconstruction in studying successful mobility at school. The research underlying this particular study constitutes analyses of the life stories Roma individuals holding or about to obtain university degrees, who have been particularly successful – by the standards of the Roma community – in the mobility channel of the education system. Social factors enabling as well as those impeding the progress of the individual, preselecting the high contingency process of social action, are highlighted in this paper. My research aims at revealing – by grasping the dynamic relationship between structure and individual – how structure as an operating mechanism affects the individual’s life, how wide manoeuvring room it leaves for upwardly mobile individual life paths and choices. Bourdieu’s social theory conclusions were tested in this research through a new approach and besides the economic and cultural dimensions of the social inequalities across social groups; the roles of social capital were also empirically studied. Particular attention was paid in the analysis to the microsocial relationships affecting the school performance of Roma students as well as to the question of secondary socialisation. Successful school mobility occurred where the family environment showed a higher degree of homophilia with the majority norms while social relationships were characterised by a higher level of heterophilia.